2015
DOI: 10.1186/s12885-015-1494-4
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of cervical intraepithelial neoplasia on the cervix in Chinese women: pooled analysis of 19 population based screening studies

Abstract: BackgroundControversy remains whether a pattern of cervical intraepithelial neoplasia exists on the cervix. Our study aims at determining if the prevalence of histologically proven lesions differs by cervical four-quadrant location or by 12 o'clock surface locations of diagnosis.MethodsWe conducted a retrospective, histopathological study of 19 different population based cervical cancer screening studies from 1999 to 2010 by Cancer Hospital of Chinese Academy of Medical Sciences. The Institutional Review Board… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…Of note, most severe lesions were found at the 8 and 7 o’clock positions, either in low- or high-grade lesions. In a similar manner, Zhao et al (2015) identified that quadrants 2 and 3, specifically in the 4 and 7 o’clock positions, were susceptible to CIN on the cervix. CIN will be found more frequently on the posterior lip than on the anterior lip of the cervix.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Of note, most severe lesions were found at the 8 and 7 o’clock positions, either in low- or high-grade lesions. In a similar manner, Zhao et al (2015) identified that quadrants 2 and 3, specifically in the 4 and 7 o’clock positions, were susceptible to CIN on the cervix. CIN will be found more frequently on the posterior lip than on the anterior lip of the cervix.…”
Section: Discussionmentioning
confidence: 74%
“…Conversely, the necrotic area may become shallower in the elderly or postmenopausal subjects due to increased tight junctional resistance. This factor becomes a major determinant for epithelial permeability that maintains the integrity and organization of cells through the action mechanism of various proteins, such as claudins ( Blaskewicz et al, 2011 ; He et al, 2012 ; Zhao et al, 2015 ). Nevertheless, in this study, no association was found between age or menopausal status with the mean depth of tissue destruction or cervical physical dimensions, including length and diameter.…”
Section: Discussionmentioning
confidence: 99%
“…To date, in terms of understanding the topographic CIN distribution with colposcopy, previous studies have qualitatively evaluated CIN lesions using limited biopsy specimens or conization specimens resected with the LEEP technique. [19][20][21][22]24,25 Most studies reported a distribution bias, mainly in the anterior or posterior walls of the uterine cervix, [19][20][21][22] whereas some investigators argued for lesion heterogeneity. 24 However, the relationship between CIN distribution and clinicopathological factors has not been accurately evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is that random biopsy was taken at fixed location on the cervix. Several studies reported there might be a topographical pattern of CIN on the cervix, which may result in underestimating the CIN2+ yield of biopsy at normal-appearing areas ( 32 - 34 ). Possible harms of taking multiple biopsies are discomfort and increased the cost of pathology processing and evaluation.…”
Section: Discussionmentioning
confidence: 99%